MENINGKATKAN KEMAMPUAN MEMBACA MELALUI PERMAINAN KATEGORI PADA ANAK USIA 5-6 TAHUN - Putri Clawson; Wulan Sari Novryanti (P3M STKIP 'Aisyiyah Riau, 2018)
This research is motivated by the low level of reading of children in Kandis One-Roof State Kindergarten. For that we need a concrete action in order to find the right way with regard to reading children, namely by playing the category. This study aims to determine whether reading skills can be improved through category play in children aged 5-6 years at TK Negeri One Roof Kandis. This type of research is classroom action research. The subjects in this study were local children B, totaling 18 children with details of 10 boys and 8 girls. From the results of the class action research and discussion as described, conclusions can be obtained towards the results of this study, namely 1) By using the application of category games can improve reading skills of children aged 5-6 years in Kindergarten One Roof Kandis. This increase occurred because every stage of the meeting was carried out improvements, so that children are accustomed to learning activities with the application of category games, 2) The ability to read children aged 5-6 in Kindergarten One Roof Kandis with the application of category games has increased every cycle. Initial data obtained a value of 40.3% with the criteria BB (undeveloped). After making improvements in the first cycle obtained a value of 55.1% with MB (starting to develop) and in the second cycle obtained a value of 78% with the criteria of BSB (Very Good Developing)